A Secured Architecture of Internet of Things (IoT) in the 5G Age - Qutaiba Ibrahim; Mustafa Haitham Mohammed; Ali Fathel Rasheed (International Journal of Mobile Computing Technology, 2025)
Internet of things (IoT) is a technology capable of connecting vast number of devices of many types worldwide via the internet using unique IP addresses. The connected devices can communicate ubiquitously anywhere, anytime for any given user. Such globally distributed networks require a high level of connectivity among its components like smart sensors, workstations as well as networking devices. Thankfully, with the aid of the recently emerged 5G technology, which offers improved characteristics in terms of capacity, reliability and coverage, the demands that IoT imposes can finally be satisfied. However, preserving the cybersecurity of 5G enabled IoT while taking advantage of its capabilities is not a trivial task. In this study, we review some of the techniques applied for the realization of IoT in 5G networks. Also, we aim at presenting a critical view about some of the recent works regarding the cybersecurity aspect of 5G based IoT. The accessibility and availability features of IoT may also give rise to various threats which may jeopardize the security of the network. This imposes a vital need to provide secure connectivity in terms of confidentiality, integrity and privacy for 5G enabled IoT in order to take full advantage of its potential.
Keywords: 5G; IOT; connectivity; layered architecture; security